Problem Aspects of Providing Informative Sovereignty of the State, Prospects and Tendencies of its Defense in Ukraine - Zadereyko, A. V.; Troyanskiy, A. V.; Vlasenko, E. V.; Задерейко, О. В.; Троянський, О. В.; Власенко, О. В.; Задерейко, А. В.; Троянский, А. В.; Власенко, Е. В. (Видавничий дім «Гельветика», 2016)
Sovereignty of the state is this political-legal property of the state, sense of that consists in its right independently to decide internal and external political questions without intervention from other states, organizations, persons. In today's realities of world pattern, the attributes of any state it is been: territory, banking system, national money, army, power, police, borders, custom etc. These attributes provide military, diplomatic, economic, political, cultural and biological sovereignties of the state. However, as far as development of virtual of communication environment (Internet) new attributes appeared in one and a half last decades - Informative and digital sovereignties of the state. The role of these attributes steadily increases and grows into key. The state could provide defense informative and digital sovereignties, it needs the complete technological chain let: processor; electronic-component base; navigational; own digital infrastructure (system, in that the Internet, television, mass-media, unite etc.). Thus the state must realize an independent management data flows (discovery, filtration, blocking, distribution). Such defense must be provided by the state and to be based on a legislative base reflecting mine-out strategy of development. In more wide sense of word informative sovereignty plugs in itself such tasks, as opposition of cultural expansion from the side of countries with the developed audiovisual infrastructure, maintenance of national and language originality. Authors proposed the measures must be accepted for providing of defense of informative and digital sovereignty of Ukraine, as state with the developed network infrastructure.

У статті розглянуто питання захисту інформаційного й цифрового суверенітетів держави як домінуючих складових частин традиційного суверенітету держави. Проаналізовано існуючі способи державного контролю щодо збереження інформаційного та цифрового суверенітетів держави. Надано рекомендації щодо захисту інформаційного й цифрового суверенітету України.

В статье рассмотрены вопросы защиты информационного и цифрового суверенитетов государства как доминирующих составных частей традиционного суверенитета государства. Проанализированы существующие способы государственного контроля по сохранению информационного и цифрового суверенитетов государства. Даны рекомендации по защите информационного и цифрового суверенитета Украины.
Проблемні аспекти забезпе- чення інформаційного суверенітету держави, перспективи та тенденції його захисту в Україні
Проблемные аспекты обеспе- чения информационного суверенитета государства, перспективы и тенденции его защиты в Украине
Keywords: attributes of the state; Research Subject Categories::LAW/JURISPRUDENCE; informative sovereignty; digital sovereignty; conception of sovereignty; informative shield; electronic shield; defense of sovereignty of the state; атрибуты государства; информационный суверенитет; цифровой суверенитет; концепция суверенитета; информационный щит; электронный щит; защита суверенитета государства; атрибути держави; інформаційний суверенітет; цифровий суверенітет; концепція суверенітету; інформаційний щит; електронний щит; захист суверенітету держави